Safety and oncological outcome of early intraoperative intravesicle mitomycin C vs. deferred instillation in patients receiving robot-assisted radical nephroureterectomy - Chou, Sheng-Feng; Lin, Wei-Ching; Chang, Han; Huang, Chi-Ping (Frontiers in Surgery, 2024)
Radical nephroureterectomy with concurrent bladder cuff excision (RNUBCE) is the gold standard surgical approach for high-risk primary upper tract urothelial carcinoma (UTUC). Given the notably high incidence of bladder tumor recurrence following this procedure, this study aimed to evaluate the effect and safety of intraoperative mitomycin-C (MMC) instillation versus deferred instillation on overall oncological outcomes following robot-assisted RNUBCE. This is a retrospective chart review study. Patients with non-invasive (N0, not T3/T4) UTUC who underwent robotic RNUBCE combined an intraoperative MMC instillation or a deferred MMC instillation after surgery at a medical center in Taiwan between November 2013 and June 2020 were eligible for inclusion. Patients with prior bladder UC, carcinomas of other origins, received neoadjuvant chemotherapy, and had undergone kidney transplantation were excluded. All surgeries were executed by a single surgical team under the guidance of the same surgeon. The primary outcomes were was the risk of bladder tumor recurrence and lympho node (LN) or distant metastasis between patients received intraoperative (IO) versus deferred MMC instillation postoperatively (PO) during one-year follow-up. The secondary outcome was postoperative adverse events assessed by the Clavien-Dindo classification. Univariate and multivariable Cox regression analyses were performed to determine the associations between study variables and the outcomes. A total of 54 patients were included in the analysis. 12 (22.2%) patients experienced a bladder tumor recurrence during follow-up (IO: 7.7%, PO: 35.7%, p<0.021). After adjustment in the multivariable, intraoperative MMC instillation was significantly associated with lower risk of bladder recurrence (adjusted hazard ratio [aHR] = 0.159, 95%CI: 0.034-0.819, p=0.02835)) but not LN/distant metastasis (aHR = 0.2740, 95%CI: 0.03-4.662.52, p=0.462249). No MMC-related Clavien-Dindo Grade III-IV adverse events were found in either group.In conclusions, iIntraoperative MMC instillation is safe and associated with a lower bladder tumor recurrence risk in patients undergoing robotic RNUBCE for UTUC than deferred instillation. Future large, prospective studies are still warranted to confirm the findings.